Sayām rop farang mư̄a khrang Krung Sī ʻAyutthayā - Kraiphop Mư̄nsǣnčhandam (Krung Thēp : Samnakphim Čhāo Phrayā, 2014)
War between Ayutthaya and other foreign countries during the 16th century.
Includes bibliographical references (pages 255-256)
In Thai.
Keywords: Phra Nakhon Si Ayutthaya (Thailand) -- History, Military -- 16th century; Thailand -- Foreign relations